Pentacoordinate Carbon Atoms in a Ferrocene Dication Derivative—[Fe(Si2-η5-C5H2)2]2+ - Shilpa Shajan; Jin-Chang Guo; Aland Sinjari; Krishnan Thirumoorthy; Venkatesan S. Thimmakondu (Chemistry, 2022)
Pentacoordinate carbon atoms are theoretically predicted here in a ferrocene dication derivative in the eclipsed-(1; <semantics>C2v</semantics>), gauche-(2; <semantics>C2</semantics>) and staggered-[Fe(Si<semantics>2</semantics>-<semantics>η5</semantics>-C<semantics>5</semantics>H<semantics>2</semantics>)<semantics>2</semantics>]<semantics>2+</semantics>(3; <semantics>C2h</semantics>) forms for the first time. Energetically, the relative energy gaps for 2 and 3 range from −3.06 to 16.74 and −2.78 to 40.34 kJ mol<semantics>−1</semantics>, respectively, when compared to the singlet electronic state of 1 at different levels. The planar tetracoordinate carbon (ptC) atom in the ligand Si<semantics>2</semantics>C<semantics>5</semantics>H<semantics>2</semantics> becomes a pentacoordinate carbon upon complexation. The ligand with a ptC atom was predicted to be both a thermodynamically and kinetically stable molecule by some of us in our earlier theoretical works. Natural bond orbital and adaptive natural density partitioning analyses confirm the pentacoordinate nature of carbon in these three complexes (1–3). Although they are hypothetical at the moment, they support the idea of “hypercoordinate metallocenes” within organometallic chemistry. Moreover, ab initio molecular dynamics simulations carried out at 298 K temperature for 2000 fs suggest that these molecules are kinetically stable.